2022
DOI: 10.3803/enm.2022.1532
|View full text |Cite
|
Sign up to set email alerts
|

Association of Shift Work with Normal-Weight Obesity in Community-Dwelling Adults

Abstract: Background: Shift work is associated with obesity and metabolic syndrome. However, this association in the normal-weight population remains unclear. This study aimed to investigate whether shift work is associated with normal-weight obesity (NWO).Methods: From the nationally representative Korea National Health and Nutrition Examination Survey (KNHANES) dataset (2008 to 2011), 3,800 full-time workers aged ≥19 years with a body mass index (BMI) ≤25 kg/m<sup>2</sup> were analysed. We defined NWO as B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It is well established that unhealthy dietary habits are associated with overweight, abdominal obesity, impairments in glucose and insulin homeostasis, abnormal lipids and lipoproteins, and elevated systemic inflammation and oxidative stress, all of which increase the risk of developing diabetes, MetS, and cardiovascular disease [ 47 ]. Fifth, a recent study [ 48 ] found that community-dwelling shift workers are prone to irregular eating times, sleep deprivation, job-related stress, and fatigue, and they are at increased risk of health conditions such as obesity, NWO syndrome, heart disease, and others by inducing hormonal changes related to circadian rhythm and appetite. However, the precise explanation(s) for the link between job conditions and NWO will be revealed in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that unhealthy dietary habits are associated with overweight, abdominal obesity, impairments in glucose and insulin homeostasis, abnormal lipids and lipoproteins, and elevated systemic inflammation and oxidative stress, all of which increase the risk of developing diabetes, MetS, and cardiovascular disease [ 47 ]. Fifth, a recent study [ 48 ] found that community-dwelling shift workers are prone to irregular eating times, sleep deprivation, job-related stress, and fatigue, and they are at increased risk of health conditions such as obesity, NWO syndrome, heart disease, and others by inducing hormonal changes related to circadian rhythm and appetite. However, the precise explanation(s) for the link between job conditions and NWO will be revealed in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have showed an increased incidence in one or several components of MetS such as a high waist circumference, elevated blood pressure, blood triglycerides and glucose levels, or low HDL cholesterol in shift workers compared with day workers [ 6 , 7 , 8 ]. Even more so, night shift work was associated with a high normal weight obesity, defined as a larger than normal percentage of fat mass, despite a normal BMI [ 9 ]. There is a wide variation of these components according to regions, race, age and gender, making comparisons more difficult and requiring a more nuanced approach of these data [ 10 , 11 , 12 , 13 ].…”
Section: Epidemiological Datamentioning
confidence: 99%
“…People with normal-weight obesity (NWO) have a weight in the normal range, but a higher amount of body fat and a higher risk of cardiovascular disease [13,14]. To investigate the relationship between shift work and NWO, Ahn et al [15] comprehensively analyzed working hours and body composition in the KNHANES dataset. Excluding some specific categories such as part-time workers, military personnel, and pregnant women, 3,800 full-time workers aged 19 or older with a BMI of less than 25 kg/m 2 were selected.…”
mentioning
confidence: 99%